Adenocarcinoma in situ do colo do útero: experiência de um centro de referência - Tavares,Mariana Vide (2016)
Overview and aims: The incidence of adenocarcinoma in situ (AIS) of the cervix is increasing, particularly in reproductive-age. Conservative treatment with cervical conization is an alternative to hysterectomy. However, concern persists regarding the risk of residual and recurrence of AIS. The purpose of this study was to determine the residual disease and outcome of patients treated for AIS. Study design: Retrospective and descriptive analysis. Population and methods: The medical records of 10 women with cervical AIS followed at the Instituto Português de Oncologia de Francisco Gentil do Porto between 1999 and 2012 were reviewed. Demographic characteristics, treatment, pathologic findings and outcomes were analyzed. Results: The mean age at diagnosis was 41.1 years (range 31-63). All patients had conization performed as the initial treatment. Negative margins after conization were noted in 30% (3/10) and one (1/3) of these had residual disease in the surgical specimen following hysterectomy. In those with positive margins, 43% (3/7) had no residual disease in the surgical specimen after histerectomy. Considering conservative treatment (2/10), a second conization was performed in one patient and showed no residual disease and the other one had no subsequent treatment. None of the patients with conservative or definitive treatment had developed recurrence or invasive disease at 33 months (range 12 to 60) of follow-up. Conclusion: Our study reinforced the evidence that conservative treatment can be performed in patients with clear margins after conization given the low persistence of disease found in surgical specimen after hysterectomy. In global, these patients had favorable outcomes without recurrence or invasive disease.